Effects of Covid-19 on fresh fruit and vegetable production, retailing and consumption in Kenya - Onyango, Kevin; Chege, Christine Gacheri Kiria; Billy, O.; Kabach, J.; Lundy, Mark M. (2021)
Following its outbreak in 2020, the COVID-19 pandemic caused multiple shocks to the Kenyan economy. The virus has affected the health and economic situation of the Kenyan population, due to virus containment restrictions, and behavioral changes such as in consumption. Certain efforts to limit the spread of COVID-19 affected Kenya's agri-food supply chain, constraining the livelihoods of millions relying on the agri-food system. This study provides evidence that articulates the pandemic's implications based on primary data collected from 3,275 households consuming fruit and vegetables in Nairobi and Kisumu, 1,289 food retailers in Nairobi and Kisumu, and 1,025 producers of fruit and vegetables from Kiambu and Kisumu Counties in Kenya. The study examines the effects of COVID-19 on different food value-chain actors. A descriptive analysis was carried out to show how households have been affected in terms of socioeconomics, food security, and nutrition. Results show a general decline in food consumption, increased food costs, a switch in food purchase location, consumption of less-preferred foods, and a sharp decline in incomes among consumers. Food retailers reported increased food prices, inconsistent commodity supplies, labor adjustments, reduced sales due to curfews and lockdowns, higher losses, and business closures. Producers also reported lower dietary diversity, shifts in primary commodities produced, reduced use of farm inputs and general reduced production. Producers additionally, expressed difficulty in financing business activities, followed by cash flow issues resulting from order cutbacks. Farmers found it increasingly difficult to support production activities due to pandemic constraints to their cash flow. Because of different effects of the pandemic on the different value-chain actors, producers, consumers, and food retailers require different policies and approaches to tackle the situation. Interventions aimed at lowering food prices will contribute to improved food security and nutrition among consumers and improve trade thereby benefitting food traders and producers. Furthermore, measures and interventions to provide resources to enterprises, such as financial support, would significantly improve food environment and trade as well as food production.